Syömisestä häiriintynyt kulttuuri : kulttuurisia tapoja tulkita syömishäiriöitä, syömistä ja syömättömyyttä - Littow, Milja (2012)
This Pro-gradu thesis is a research about eating disorders and more widely about binging and dieting in our current Western culture. Eating disorders and the problematic relationship between women and food has become more common in our culture. Nowadays media is filled with food programs and commercials where women are shown to have certain obsessive relation with food.